Kozma Soldatenkov (1818–1901) and His Gallery of Russian Artists: the Origins of the Collector’s Worldview and the Peculiarities of His Collection - Kuznetsova, Marfa V. (Actual Problems of Theory and History of Art, 2023)
The collection of the Moscow merchant Kozma Soldatenkov (1818–1901), although known to researchers, has not been considered in the context of the range of aesthetic and philosophical ideas that formed the merchant’s worldview in the 1840s and 1850s. Meanwhile, many of the postulates of the leading intellectuals of the time determined the vector of development of the collection, which was compiled for over forty years. These were the ideas of the most famous representatives of the Moscow circle of Westerners, who adopted the theses of Hegelian aesthetics and focused on the idealistic notion of the historical development, as well as the need to reflect the so-called “folk spirit” in art. Among them were Vasily Botkin’s statements on the importance of historical ideals of the past and present in painting, which were reflected in Soldatenkov’s acquisitions, the analysis of which has allowed us to identify them not as a heterogeneous collection, but as a conceptually unified one, the result of a conscious collecting activity.